2019
DOI: 10.1097/scs.0000000000005733
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Prognosis in Patients With Spontaneous Supratentorial Intracerebral Hemorrhage Under Medical and Surgical Treatment

Abstract: Spontaneous intracerebral hemorrhage (ICH) is a vascular brain disease that causes very high rates of death and disability. Whether surgical or medical treatment is more appropriate is controversial. The purpose of the study was to examine the morbidity and mortality rates of surgical and medical therapy and their differences in order to determine which patients should be operated. In our study, the authors selected randomly and evaluated retrospectively 49 patients who were operated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…More attention should be given to ICH patients with the abovementioned imaging characteristics to obtain a good prognosis. According to previous reports, intracranial hemorrhage rupture into the ventricle is a predictor of poor prognosis [26]. Our univariate analysis and multivariate analysis showed that the IVH relationship was an independent predictor of prognosis.…”
Section: Discussionsupporting
confidence: 64%
“…More attention should be given to ICH patients with the abovementioned imaging characteristics to obtain a good prognosis. According to previous reports, intracranial hemorrhage rupture into the ventricle is a predictor of poor prognosis [26]. Our univariate analysis and multivariate analysis showed that the IVH relationship was an independent predictor of prognosis.…”
Section: Discussionsupporting
confidence: 64%
“…Hematoma volume is another important indicator of the severity of spontaneous ICH. Cerebral hemorrhage volume and level of consciousness are determinants of short-term prognosis [25][26][27][28] . Previous reviews have shown that minimally invasive surgery is appropriate for hematomas with a volume of 25-40 mL, while hematomas > 40 mL require other forms of treatment, such as craniotomy 1,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…For many years, the GCS score has been used as an important criterion for assessing the severity of acute traumatic brain injury, as it provides a comprehensive index of neurologic impairment of patients with craniocerebral injury. It is also one of the most important clinical indicators for determining the indications for surgery and predicting prognosis 25 . The GCS score has shown some correlation with rebleeding rate, especially in non-comatose patients and nonsurgical patients, and it correlates with various factors that in uence rebleeding in patients with hypertensive cerebral hemorrhage, such as patient age, blood pressure, blood glucose, and hematoma volume.…”
Section: Discussionmentioning
confidence: 99%
“…[2], [5] Thus, sICH has been declared the world's third most common cause of death. [6] Various modalities of patient management, both conservatively and surgical, have been studied and continue to be developed to increase patient safety with intracerebral hemorrhage. [7] Surgery in sICH is aimed at removing clots while relieving tissue injury, decreasing local ischemia, and lowering intracranial pressure.…”
Section: Introductionmentioning
confidence: 99%